Reading in Print and Digital Texts: Towards a Semiotically Integrated Didactic Approach - Alessandra Natalini; Fabio Orecchio (Language, Literature and Education: Research Updates Vol. 1, 2025)
Through a literature review, this paper examines the relationship between paper and digital texts, highlighting their distinctive features and their role in teaching and learning processes. The methodological approach of the research is qualitative, using semi-structured interviews as tools for data collection. It also describes the results of research on how young readers engage with written and digital texts. The study reveals that readers of paper texts were introduced to reading by family members or their social circle, while those who prefer digital texts report having been less encouraged to read paper texts. Almost all the children emphasized the importance of decoding paper texts and reported discussing what they read with other interested readers. The research clearly indicates that schools need to expand the design of integrated reading spaces to encourage children to appreciate different types of texts and to enhance the various ways in which they are understood.